Nuclear factories for signalling and repairing DNA double strand breaks in living fission yeast - Meister, Peter (Oxford University Press, 2003)
In mammalian and budding yeast cells treated with genotoxic agents, different proteins implicated in detecting, signalling or repairing DNA lesions form nuclear foci. We studied foci formed by proteins involved in these processes in living fission yeast cells, which is amenable to genetic and molecular analysis. Using fluorescent tags, we analysed subnuclear localisations of the DNA damage checkpoint protein Rad9, of the homologous recombination protein Rad22 and of PCNA, which are implicated in many aspects of DNA metabolism. After inducing double strand breaks (DSBs) with ionising radiations, Rad22, Rad9 and PCNA form a low number of nuclear foci. Rad9 recruitment to foci depends on the presence of Rad1, Hus1 and Rad17, but is independent of downstream checkpoint effectors and of homologous recombination proteins. Likewise, Rad22 and PCNA form foci despite inactive homologous recombination repair and impaired DNA damage checkpoint. Rad22 and Rad9 foci co-localise completely, whereas PCNA co-localises with Rad22 and Rad9 only partially. Foci do not disassemble in cells unable to repair DNA by homologous recombination. Thus, in fission yeast, DSBs are detected by the DNA damage checkpoint and are repaired by homologous recombination at a few spatially confined subnuclear compartments where Rad22, Rad9 and PCNA concentrate independently.